2001
DOI: 10.1210/endo.142.7.8238
|View full text |Cite
|
Sign up to set email alerts
|

The Maternal Diet during Pregnancy Programs Altered Expression of the Glucocorticoid Receptor and Type 2 11β-Hydroxysteroid Dehydrogenase: Potential Molecular Mechanisms Underlying the Programming of Hypertension in Utero*

Abstract: Potential mechanisms underlying prenatal programming of hypertension in adult life were investigated using a rat model in which maternal protein intake was restricted to 9% vs. 18% casein (control) during pregnancy. Maternal low protein (MLP) offspring exhibit glucocorticoid-dependent raised systolic blood pressure throughout life (20-30 mm Hg above the control). To determine the molecular mechanisms underlying the role of alterations in glucocorticoid hormone action in the prenatal programming of hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
4
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(113 citation statements)
references
References 44 publications
7
97
4
5
Order By: Relevance
“…Renal glucocorticoid receptor expression [17] and the ratio of angiotensin II AT 1 /AT 2 receptors [29] are increased in LP rats. By standardizing the endocrine input to the kidney, we may have stimulated a greater response in the LP rats compared with control animals, which is a limitation of our approach.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Renal glucocorticoid receptor expression [17] and the ratio of angiotensin II AT 1 /AT 2 receptors [29] are increased in LP rats. By standardizing the endocrine input to the kidney, we may have stimulated a greater response in the LP rats compared with control animals, which is a limitation of our approach.…”
Section: Discussionmentioning
confidence: 90%
“…In the LP model, NHE-3 and ENaC are unaltered but NKCC2 and, in some reports, NCC are increased [14][15][16]. One group also described increased renal Na + :K + adenosine triphosphatase (ATPase_-α 1 and-β 1 subunit messenger RNA (mRNA) expression in LP rat kidneys [17], whereas we have shown that whole-kidney Na + :K + ATPase pump activity and expression of the α 1 subunit in the inner medulla are reduced markedly [15]. Most attention has focussed on the increase in NKCC2 mRNA and protein expression in the TAL of the LP rat, as this might be expected to result in renal sodium retention and thus an increase in blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work found that maternal protein restriction leads to down-regulation of 11b-hydroxysteroid dehydrogenase-2 in placenta and consequently, increased foetal exposure to maternal glucocorticoids [19,20,25,26]. This has been proposed to underlie the effects of low-protein diet on offspring phenotypes such as development of hypertension [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…This has been proposed to underlie the effects of low-protein diet on offspring phenotypes such as development of hypertension [20,23]. Glucocorticoid excess has been linked to clinical observations associated with the metabolic syndrome such as central obesity, hypertension, hyperlipidaemia and glucose intolerance [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation